2023
DOI: 10.1021/acs.analchem.2c04327
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Periodontal Disease Marker with Geometrical Transformation of Ag Nanoplates

Abstract: Alkaline phosphatase (ALP) and interleukin-1beta (IL-1β) are crucial salivary biomarkers for the diagnosis of periodontal disease that harms the periodontal tissue along with tooth loss. However, there has been no way of sensitive and portable detection of both biomarkers in saliva with multivariate signal readout. In this work, we design the multicolorimetric ALP and IL-1β sensing platform based on geometrical transformation of silver nanoplate transducer. By utilizing enzymatic activity of ALP that dephospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…[41] Given its association with numerous diseases, [42] abnormalities in ALP activity serve as important biomarkers for clinical diagnosis and treatment. [43][44][45][46][47][48][49][50] Hence, the visual detection of low abundance biomarker of ALP has garnered significant attention in the fields of diagnostics and biomedical research.…”
Section: Enrichment and Cycling Amplification Strategies For Femtomol...mentioning
confidence: 99%
“…[41] Given its association with numerous diseases, [42] abnormalities in ALP activity serve as important biomarkers for clinical diagnosis and treatment. [43][44][45][46][47][48][49][50] Hence, the visual detection of low abundance biomarker of ALP has garnered significant attention in the fields of diagnostics and biomedical research.…”
Section: Enrichment and Cycling Amplification Strategies For Femtomol...mentioning
confidence: 99%
“…In addition to anisotropic gold nanostructures, silver nanostructures can also serve as the substrates for plasmonic immunoassays. For instance, Kim et al reported a plasmonic immunoassay for the detection of periodontal disease marker interleukin-1 beta (IL-1 β ) with the ALP-triggered geometrical transformation of Ag triangular nanoplates (AgNPLs) ( Figure 20 D) [ 154 ]. In this work, PAP reduced Ag + into Ag seeds on the high-energy edge of AgNPLs, eventually resulting in the shape transformation from triangular to hexagonal, rounded pentagonal, and finally spherical.…”
Section: Colorimetric Immunoassaysmentioning
confidence: 99%
“…Copyright 2019 American Chemical Society. ( D ) Schematic illustration of the plasmonic immunoassay for detection of IL-1 β with ALP-triggered geometrical transformation of AgNPLs [ 154 ]. Copyright 2023 American Chemical Society.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…Therefore, it is of great significance for biomedical diagnoses to construct a simple, sensitive, and accurate biosensor to monitor ALP activity. Many approaches have been established for the measurement of ALP activity, including surface-enhanced Raman scattering [ 6 ], colorimetry [ 7 , 8 , 9 ], electrochemistry [ 10 , 11 ], chromatography [ 12 ], chemiluminescence [ 13 ], electrochemiluminescence [ 14 ], and fluorescence [ 5 , 15 , 16 ] strategies. Among these methods, fluorescent methods with high sensitivity, fast response times, and real-time detection capability have attracted particular interest [ 5 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%